2019
DOI: 10.1590/s1983-41952019000100009
|View full text |Cite
|
Sign up to set email alerts
|

Pervious concrete: study of dosage and polypropylene fibers addiction

Abstract: The use of pervious concrete to minimize the effects caused by the impermeability of the soil as a result of increasing urbanization is an alternative that still requires further studies regarding its design and implementation. From this perspective, this paper presents a study of the characteristics of pervious concrete, including its tensile strength, compressive strength, flexural strength and the permeability coefficient, through the development of various mixtures to adjust the characteristics of the loca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
2
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(6 citation statements)
references
References 12 publications
1
2
0
3
Order By: Relevance
“…The authors in ( 6) and ( 31) noticed the importance of compaction. In (31), in conclusion it stands: "… mechanical compaction should be used so that the mechanical properties are improved…". As can be seen in Figure 8, the positive effect of fibre addition was more emphasised in the case of vibrated mixtures -i.e., mechanical properties of vibrated mixtures with incorporated fibres (HV, GV, CV, PPV) achieved higher relative values with respect to their reference mixture (EV) than mixtures compacted with wooden lath and hammer (H, G, C, PP) with respect to their reference mixture (E).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The authors in ( 6) and ( 31) noticed the importance of compaction. In (31), in conclusion it stands: "… mechanical compaction should be used so that the mechanical properties are improved…". As can be seen in Figure 8, the positive effect of fibre addition was more emphasised in the case of vibrated mixtures -i.e., mechanical properties of vibrated mixtures with incorporated fibres (HV, GV, CV, PPV) achieved higher relative values with respect to their reference mixture (EV) than mixtures compacted with wooden lath and hammer (H, G, C, PP) with respect to their reference mixture (E).…”
Section: Resultsmentioning
confidence: 99%
“…Enhanced porosity, which influences structural and functional properties of pervious concrete (23), leads to applications where the acoustic absorption or storm water runoff control is needed. To widen the application of this kind of concrete, researches are continuously working on the development of porous concrete with enhanced properties such as high performance pervious concrete (24)(25)(26) or fibre reinforced pervious concrete (27)(28)(29)(30)(31)(32). Zhong and Wille (33) analysed and discussed the influence of fibre reinforcement on the freeze-thaw durability of pervious concrete and concluded that the improvement can be achieved through the incorporation of fibres into high performance pervious concrete matrix.…”
Section: Introductionmentioning
confidence: 99%
“…Consequentemente, a variedade de materiais de construção disponíveis, incluindo concreto, evoluiu significativamente e melhorou desde então (MARTINS FILHO et al, 2020). De acordo com Pils et al (2019), ao adicionar água a essa mistura, a mistura solta de cimento e agregados minerais se transforma em uma mistura mais espessa e sólida. As relações água / cimento podem ir de concreto de alta resistência, para 8,5 a 1 para uma mistura de baixa resistência.…”
Section: Concreto: Conceitos Gerais E Definiçõesunclassified
“…É possível projetar a propriedade da mistura com base no uso pretendido adicionando aditivos. Pils et al (2019) definem aditivos como um composto químico que é adicionado em pequena proporção à mistura de concreto para produzir uma característica desejada. Os tipos de aditivos usados são aceleradores, retardadores de pega e redutores de água.…”
Section: Concreto: Conceitos Gerais E Definiçõesunclassified
“…No geral foi constatado que o uso de fibras tem influência insignificante para a resistência à compressão (ALIABDO;ABD ELMOATY;FAWZY, 2018;REHDER;BANH;NEITHALATH, 2014). Correlações positivas foram encontrados para a resistência à tração verificados pelos ensaios de flexão e tração por compressão diametral (HESAMI;AHMADI;NEMATZADEH, 2014;PILS et al, 2019;WANG et al, 2006). De acordo com Rehder, Banh e Neithalath (2014), as fibras irão atrasar a abertura, propagação e coalescência de algumas fissuras, deste modo acomodando uma abertura maior de fissura antes da falha total.Foi mostrado por Rehder, Banh e Neithalath (2014) e Pils et al (2019) que para algumas condições de traço e porosidade a adição de fibras irá diminuir a resistência a compressão, entretanto os benefícios do aumento na tração ainda sim deixa o uso delas atrativo.…”
unclassified